VALIDITY AND RELIABILITY OF SHORTENED GENERAL COMFORT QUESTIONNAIRE IN INDONESIAN VERSION - Eria Riski Artanti; Intansari Nurjannah; Subroto Subroto (Belitung Raya Foundation, Indonesia, 2018)
Background: Comfort is one of nurses’ concerns in each of nursing care activity. There are several different instruments to measure patient’s comfort. Tools regarding comfort however, have not been developed and tested in Indonesian. Objectives: This study aimed to assess the validity and reliability of the Shortened General Comfort Questionnaire (SGCQ) in Indonesian version. Methods: SGCQ was translated and back translated to Indonesian before it was used for this study. Three experts (two lecturers and one clinician) were recruited to measure the content validity of SGCQ in Indonesian version. S-CVI and I-CVI analyses were used to measure the content validity of this instrument, and Pearson correlation was used for the construct validity. Content validity of instruments consists of relevance, accuracy, clarity, credibility and equivalency. Reliability analysis of this instrument was performed using Cronbach’s alpha in 71 patients undergoing hemodialysis. Results: Result show that an I-CVI score was 1, which implies that each item of relevance, accuracy, clarity, credibility, and equivalency was acceptable. In addition, the S-CVI score was also 1, which implies that the validity of this instrument was acceptable. Cronbach’s alpha score was also showed 0.769 means that the SGCQ instrument in the Indonesian language is reliable because the score was in the range of 0.7–0.95. Conclusion: SGCQ in Indonesian version has acceptable validity and reliability and it can be used to measure patient’s comfort level in Indonesian.